Pembelajaran Pendidikan Agama ISlam (PAI) Dengan Menggunakan Media Android di SDN 1 Metro Barat Kota Metro - Malik Mar’an, Fadzkur Abdul; Akla, Akla; Ali, Muhammad (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2021)
This study aimed to provide a learning experience for students by using Android media so that it could improve students' motivation. With implementing learning by using android media, students were very enthusiastic in following the learning process delivered by the teacher. Students were also easier to understand the material delivered by the teacher. The research used experiment method pree test post-test design model that was giving treatment to student’s groups with the implementation of android media during several meetings. The sample of this study was 20 students of the fifth grade of Elementary School 1 West Metro, Metro City. Data collection techniques were tests, observations, and interviews. Instrument aimed for students to get learning outcomes. The observation was used to see the Islamic education learning process by using android media. The interview was aimed at the teacher in using additional data about student activities in the learning process. Research results showed that the learning process using Android media has increased the learning joy and enthusiasm of students. Joy and enthusiasm encouraged students to be active in each learning process and had an implication for the achievement of learning objectives. Statistics test results showed that the use of android media in Islamic education learning had a significant influence on student learning outcomes.